Exploiting DELLA Signaling in Cereals. (October 2017) - Van De Velde, Karel; Ruelens, Philip; Geuten, Koen; Rohde, Antje; Van Der Straeten, Dominique
Abstract : The spectacular yield increases in rice and wheat during the green revolution were partly realized by reduced gibberellin (GA) synthesis or sensitivity, both causing the accumulation of DELLA proteins. Although insights into the regulation of plant growth and development by DELLA proteins advanced rapidly in arabidopsis ( Arabidopsis thaliana ), DELLA-mediated regulation of downstream responses in cereals has received little attention to date. Furthermore, translating this research from arabidopsis to cereals is challenging given their different growth patterns and our phylogenetic analysis which reveals that DELLA-related DGLLA proteins exist in cereals but not in arabidopsis. Therefore, understanding the molecular basis of DELLA function in cereals holds great potential to improve yield. In this review, we propose to extend the focus of DELLA functional research to cereals, and highlight the appropriate tools that are now available to achieve this. Trends: DELLA proteins translate internal and environmental signals into a plethora of growth and developmental responses through their interaction with specific DELLA-interacting proteins (DIPs). Cereal yield has been improved by genetically and chemically increasing DELLA protein levels, but its application is currently limited by undesired pleiotropic effects. The DELLA degradation mechanism has been elucidated in arabidopsis and cereals, but most studies on DELLA–DIP interactions have been conducted in arabidopsis. Understanding DELLA function in cereals can unlock its functional portfolio for cereal crop improvement. The required molecular tools, such as genome editing, digital single-cell analysis, and the crystal structure of DELLA-related proteins, as well as genetic and genomic cereal resources, have recently become available.